Persfektif Budaya Jawa dalam Syair Lagu Campursari dan Implementasinya pada Pembelajaran Sosiolinguistik - Dessy Saputry; Umi Kholidah (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2022)
This study aims to describe the perspective of Javanese culture in the poetry of campursari songs and its implementation in sociolinguistic learning at the Muhammadiyah University of Pringsewu Lampung. The method used is the descriptive qualitative method. The results show that the Javanese cultural perspective consists of wayang mythology which includes the concepts of jumbuhing kawula gusti and sangkal paran; the slametan ritual includes social and religious aspects; Javanese ethics, namely the attitude of narima, being patient or aja kesusu-susu, tepa selira, aja ngaya, and aja srakah. This concept is implemented in the Sociolinguistics course by guiding language speakers (teachers) on how to use language in their lives by showing the language, variety of languages, or language styles used when talking to certain people at a specific place and time. In conclusion, the Javanese cultural perspective in the campursari song contains three aspects, namely wayang mythology, slametan, and Javanese ethics. Elements in the music become a guide on using language in life. Keywords: Javanese Culture, Sociolinguistics, Campursari Song Lyrics